Sound Art in Malaysia from a Malaysian Sound Artist Perspective - Hasnizam, Abdul Wahid (Malaysian Music Journal, 2013)
Early exploration of the use of computers in Musical Instrument Digital Interface (MIDI), somehow allowed me to venture further into the domain of sound. Nothing much was known or noted in terms of the notion or historical perspectives of electroacoustic music in Malaysia. Unlike in the West, our music industry accommodated Western music, particularly popular music, but not experimental or electroacoustic music. The advancement in computer technology in music applications introduced new creative ideas, and its democratization permitted more creative exploration, technically and aesthetically. This paper is a recollection of the long journey of a Malaysian composer venturing into electroacoustic music.